Study on Degradation of Azithromycin Antibiotics by Molybdenum Sulfide Graphene Oxide Composites under Visible Light. Issue 1 (March 2020) - Li, Changyan; Jin, Huihui; Hou, Zepeng; Guo, Yan
Abstract: Waste water including azithromycin antibiotics could cause environment to generate antibiotics bacteria, which heavily damage the ecological balance. It is necessary to study the degradation of azithromycin antibiotics. Molybdenum sulfide graphene oxide composites were synthesized by hydrothermal method. Owing to their better conductivity, the photocatalytic performance of molybdenum sulfide graphene oxide composites for azithromycin was evaluated in the visible-light range. The results show that the degradation rates of molybdenum sulfide and molybdenum sulfide graphene oxide composites to 100 mg/L azithromycin were 87% and 75%, respectively after 180 min of visible light irradiation. Molybdenum sulfide graphene oxide composites show better azithromycin degradation property.